User acceptance of Online Banking Service in Australia - Heng, Paul Ping Yeow; Yuen, Yee Yen; Tong, David Yoon Kin; Lim, Nena (2008)
The research investigates both positive and negative factors influencing user acceptance of online banking services (OBS) in Australia. A research framework was developed based oil the Unified Theory of Acceptance and Use of Technology (UTAUT). One hundred and ninety respondents in Australia participated in a survey on their perceptions toward OBS. Results show that although respondents strongly believe that using OBS would benefit their daily life, Many issues (Such its Security concerns and technology anxieties) reduce their self-efficacies. Recommendations were given to promote it safe, efficient and conducive environment for User adoption of online banking.